2014
DOI: 10.1111/age.12133
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide association analysis for growth, muscularity and meat quality in Piétrain pigs

Abstract: Improvement in growth and meat quality is one of the main objectives in sire line pig breeding programmes. Mapping quantitative trait loci for these traits using experimental crosses and a linkage-based approach has been performed frequently in the past. The Piétrain breed often was involved as a founder breed to establish the experimental crosses. This breed was selected for muscularity and leanness but shows relatively poor meat quality. It is frequently used as a sire line breed. With the advent of genome-w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 28 publications
0
24
0
Order By: Relevance
“…Genomic tools are increasingly important in livestock conservation and selection (Lenstra et al 2012). Pietrain is under strong management regarding pig performance; therefore, clear selection signals are present in the population (Stratz et al 2014). We have shown that selection signatures are weakened when the focus is solely on optimizing diversity.…”
Section: Impact Of Management On Selection Goalsmentioning
confidence: 89%
“…Genomic tools are increasingly important in livestock conservation and selection (Lenstra et al 2012). Pietrain is under strong management regarding pig performance; therefore, clear selection signals are present in the population (Stratz et al 2014). We have shown that selection signatures are weakened when the focus is solely on optimizing diversity.…”
Section: Impact Of Management On Selection Goalsmentioning
confidence: 89%
“…The same filtering criteria as in Stratz et al . () were used to compare the results of both studies. Genotypes from individuals were filtered with respect to call rate (removal of SNPs with a call rate less than 95%), parent–progeny conflicts (removal of SNPs with parent–progeny conflict greater than 2%), MAF (exclusion of SNP with a minor allele frequency less than 3%) and significant deviation from the Hardy–Weinberg equilibrium (p ‐ value < 0.0001).…”
Section: Methodsmentioning
confidence: 99%
“…It can be speculated that sites in the genome at which we know selection has occurred (Stratz et al . ) coincide with selective sweeps (Qanbari et al . ).…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations